Variations in cell wall traits impact saccharification potential of Salix famelica and Salix eriocephala. (May 2021) - Murphy, Emily K.; Mottiar, Yaseen; Soolanayakanahally, Raju Y.; Mansfield, Shawn D.
Abstract: Increasing global populations, finite arable land, and the anthropogenic release of carbon dioxide into the atmosphere are driving the search for bio-based alternatives to the petroleum-derived fuels and chemicals that underpin the global economy. With rapid growth rates, a propensity for coppicing, and a wide geographic range across Canada, native shrub willows ( Salix spp.) are an attractive source of low-input, high-volume biomass. To date, most willow research has focused on increasing yields and improving cropping systems, while comparatively little work has been done to assess the intrinsic diversity in cell wall traits and bioenergy potential. In this study, we characterized the cell wall composition and wood ultrastructure of 338 xylem samples from two Canadian willow species, Salix famelica and Salix eriocephala, harvested from a common garden experimental plot. Lignin content ranged from 17.5–25.1% in S. famelica and 18.6–24.3% in S. eriocephala . Following alkali pretreatment with 62.5 mM NaOH at 90 °C for 3 h and a 70-h enzymatic digestion with Accellerase 1000, glucose release ranged from 23.0–38.9 wt% in S. famelica and from 20.5–37.7 wt% in S. eriocephala, while xylose release ranged from 9.4–14.9% in S. famelica and from 9.5–15.2% in S. eriocephala . Partial least squares regression modelling showed that lignin content and composition were important negative regulators of glucose release. Overall, this work highlights the innate variability in cell wall traits of native willows and identifies potential genotypes that should be considered in future breeding and deployment strategies for Canadian bioenergy production. Highlights: Extensive assessment of 11 cell wall traits in Salix famelica and Salix eriocephala . Significant interspecific variation in cell wall composition and wood ultrastructure. Alkali pretreatment outperformed acid pretreatment in saccharification potential. Glucose release was strongly impacted by lignin content and composition. Saccharification potential was largely unaffected by wood ultrastructure.